PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI MOLEK (MONOPOLI EKONOMI) BERSISTEM OPERASI ANDROID - Hanif Prasetya (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
AbstractThe background of this research is about the importance of mastery of learning media for educators in delivering learning materials. The purpose of the study was to determine the feasibility of monopoly learning media, interest in learning and student responses. This research involves material experts and media experts. This research uses the type of research development or Research and Development (R&D) with the development model used is ADDIE The development model used is ADDIE which consists of 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. MOLEK (Economic Monopoly) learning media is an Android-based mobile learning. To measure interest, use a questionnaire with a score of positive and negative statements, while to measure student responses the Guttman scale is used. Implementation of Economic Monopoly Learning Media Implementation of Economic Monopoly Learning Media in class XI students of SMA Muhammadiyah 3 Surabaya was carried out for 20 students. Based on the research results, the development of MOLEK (Economic Monopoly) Learning Media on Monetary and Fiscal Policy Materials in Senior High Schools is declared valid, practical and significant. Validation by material experts got a score of 84% while validation by media experts got a score of 84%. The analysis of student response data obtained a score of 91.5%, it can be concluded that the application of MOLEK (Economic Monopoly) learning media received a very decent response from students.Keywords: Android-based mobile learning, monopoly learning media, interest in learning and student responses